Lockeans Maximize Expected Accuracy. Issue 509 (12th December 2017) - Dorst, Kevin
Abstract: The Lockean Thesis says that you must believe p iff you're sufficiently confident of it. On some versions, the 'must' asserts a metaphysical connection; on others, it asserts a normative one. On some versions, 'sufficiently confident' refers to a fixed threshold of credence; on others, it varies with proposition and context. Claim: the Lockean Thesis follows from epistemic utility theory —the view that rational requirements are constrained by the norm to promote accuracy. Different versions of this theory generate different versions of Lockeanism; moreover, a plausible version of epistemic utility theory meshes with natural-language considerations, yielding a new Lockean picture that helps to model and explain the role of beliefs in inquiry and conversation. Your beliefs are your best guesses in response to the epistemic priorities of your context. Upshot: we have a new approach to the epistemology and semantics of belief. And it has teeth. It implies that the role of beliefs is fundamentally different from what many have thought, and in fact supports a metaphysical reduction of belief to credence.